Andean integration is reborn from Cusco: The restoration of the Almudena Bridge - GUERRA VERA, YADIRA (2017)
This article presents an architecture critique about the result of the La Almudena Bridge Restoration and Value Enhancement project in the city of Cusco, which ended the year 2006. Said project starts from the idea of physically recovering the historical Inca road system, the Qhapaq Ñan, that was once the crucial integration tool of the then empire of the Tawantinsuyu. The realization of the project also meant the renovation of a space under a marked deterioration and insalubrity process. As well, it caused the reopening of the access through which Cusco communicates with the Kuntisuyu, or coastal, territories. Unexpected challenges and new methodological experiences appeared during the intervention, and a new way to understand the value of public civil transportation heritage was born, previously not truly appreciated.